Coping Strategies of Farm and Ranch Men - Harriet K. Light; Ruth E. Martin; Doris Hertsgaard (Journal of Research in Rural Education, 1990)
Although farm life has long been considered an ideal lifestyle for many Americans, chan~es in rural. America now threaten both the concept and the reality. This article reports on a stUdy of the copmg strategies of 258 randomly selected farmers and ranchers in a midwest state. These farmers and ranchers were reluctant to accept help from professionals, neighbors or relatives. They were confident in their abilities to seek independent solutions to their difficulties. These findings can be helpful to those consituents who serve the needs of farm and ranch men